Analysis of the Research Words Devoted to the Study of Phraseological Units Expressing Financial Position of a Man in Different Languages - Shukurova Zahro Farxodovna (Researchparks Publishing, 2022)
Given article is dedicated to the major problems and issues of phraseological studies and discusses scientific study of idioms, moreover states clear examples on this field.